Simultaneous saccharification and fermentation with delayed yeast extract feeding and in-situ recovery for biobutanol production from oil palm empty fruit bunch - Mohamed Salleh, Muhammad Siddiq (2018)
Oil palm empty fruit bunch (OPEFB) is an abundant waste generated from palm oil mill processing after extraction of palm oil from fresh fruit bunch (FFB). OPEFB contributes about a quarter of the oil palm biomass generated equivalent to 23 million tonnes per year. This abundant and sustainably produced lignocellulosic biomass could be one of the potential biomass feedstocks for biofuel production such as biobutanol. Biobutanol is appealing to researchers as it has higher energy content and lower volatility as compared to bioethanol and biomethanol. However, utilising OPEFB as raw material for biobutanol production has several challenges including multiple processing steps, low biobutanol concentration and yield which lead to inefficient biobutanol production and recovery. In order to overcome these problems, several bioprocessing strategies were evaluated in this study. Three types of impeller have been used with and without baffle in order to obtain a good OPEFB homogeneity in the 2-L bioreactor during saccharification. It shows that, pitched turbine impeller without baffle shows better efficiency of homogeneity with 31.98 g/L reducing sugar. Simultaneous saccharification and fermentation (SSF) process was applied in order to reduce the processing steps by combining saccharification and fermentation simultaneously in a single operation in the same reactor. From this study. approximately 2.88 g/L of biobutanol produced from SSF as compared to 2.86 g/L of biobutanol produced from separate hydrolysis and fermentation (SHF). Although the biobutanol concentrations are almost similar, SSF shows better performance in term of process duration, reducing the apparatus and labour needed. However, the biobutanol concentration is still considered low, which is due to acid accumulation caused by slow acid reassimilation for solventogenic phase. Therefore, delayed yeast extract feeding (DYEF) was introduced in the SSF to reduce acids and enhance the biobutanol concentration. DYEF was conducted by introducing yeast extract after 39 h of SSF operation instead of adding the yeast extract at the beginning of the fermentation, resulted with an increase of 46% of biobutanol titre. The process was further enhanced up to 26% by implementing in-situ recovery using a gas stripping to reduce the solvents inhibition. The in-situ recovery using gas stripping had successfully recovered 20 g/L of biobutanol with 83% purity. In overall, this study had improved the biobutanol production with 72% increment (0.16 biobutanol yield, 0.056 g/L/h of productivity), by conducting SSF with DYEF and in-situ recovery.